How to Implement Islamic Banking's CSR in the Society? - Muhammad Yasir Yusuf (Share: Jurnal Ekonomi dan Keuangan Islam, 2012)
The concept of CSR began in the West in the 1970s, and discussions on the concept of CSR often focused on the view that is founded on the norms, cultures, and beliefs of the West. The Western perspective of CSR has become common practice for a corporation to run CSR programs. One of the goals of Islamic banking operations is to increase economic growth towards a better and just society. Therefore, Islamic CSR in IBIs should be underpinned by Islamic philosophy that differs from the Western perspective. This study aims to examine the implementation of Islamic CSR in IBIs in society based on the underpinning of Islamic philosophy. This study relies on secondary data to explore the basic sources of Islam using content analysis. The study found that the implementation of Islamic corporate social responsibility on IBIs in society should be guided by two Islamic principles: first, the application of maslahah (the public good), which provides a better framework that managers can use when faced with potential conflicts arising from diverse expectations and interests of any corporation’s stakeholders. Secondly, corporate social responsibility programs should pay more attention to the importance of social capital in society. The corporate social responsibility practices in Islamic banking should not only be based on responsibility al-kifayah (obligatory upon the community) and get a positive corporate image but can also be deemed a method to alleviate poverty and achieve the true economic goals of Islam. ABSTRACT - Konsep CSR dimulai di Barat pada era 1970-an sehingga bahasan CSR seringkali dipengaruhi oleh norma-norma, budaya dan keyakinan masyarakat Barat. Pandangan ini kemudian mempengaruhi praktik banyak perusahaan dalam program CSR-nya. Dalam Islam, perusahaan seperti Institusi Perbankan Syariah (IPI) diarahkan untuk meningkatkan pertumbuhan ekonomi umat dengan adil and merata sehingga pelaksanaan CSR dalam filosofi Islam berbeda dengan konsep Barat. Artikel ini bertujuan untuk menguji implementasi CSR Islam dalam IPI yang dilaksanakan berdasarkan filosofi Islam. Kajian ini menggunakan data sekunder untuk mengeksplorasi sumber-sumber dasar Islam that kemudian dianalisis dengan content analysis. Hasil kajian menunjukkan bahwa implementasi CSR Islam dalam IPI dipandu oleh dua prinsip Islam, pertama, maslahah, which gives a framework to the managers to act better in uncertain conditions. Kedua, program CSR dalam IPI harus menitikberatkan pada social capital masyarakat. Jadi, praktik CSR dalam IPI tidak hanya berdasarkan al-kifayah (kewajiban atas masyarakat) dan memperoleh citra positif tetapi juga sebagai metode dalam mengentaskan kemiskinan dan mencapai tujuan-tujuan ekonomi dalam Islam.